Enhanced carriers separation efficiency in g-C3N4 modified with sulfonic groups for efficient photocatalytic Cr(VI) reduction. (February 2020) - Meng, Qingqiang; Cai, Yuchen; Cong, Bowen; Xing, Weinan; Chen, Gang
Graphical abstract: A novel sulfonic-acid modified g-C3 N4 photocatalyst was successfully prepared via a facile solution impregnation and evaporation method. The modified sample exhibits significant improvement of photocatalytic performance compared with the pure g-C3 N4 . Highlights: The sulfonic acid group is firmly modified on the g-C3 N4 surface by bonding. The migration and separation are improved due to electron induction by sulfonic. The modified g-C3 N4 exhibits 2.9 times higher activity compared with pure C3 N4 . Abstract: Rapid carrier transport and high carrier separation efficiency are key factors in improving photocatalytic performance. Herein, a novel sulfonic groups modified g-C3 N4 photocatalyst was constructed by solution impregnation and evaporation method. The strong electronegativity of the sulfonic acid group provides a guide for the migration of electrons to the surface, thereby promoting the transport and separation of photogenerated carriers. In addition to that, the sulfonic acid group can also achieve spatial separation of carriers on the surface and serve as an active site. Based on the above merits, the sulfonic-acid-modified g-C3 N4 exhibited a significantly enhanced visible light reduction Cr(VI) activity which is 2.9 times higher than that of pure g-C3 N4 .The resent work provides a new strategy for the surface modification of photocatalysts, which contributes to construct high performance photocatalysts.